Efektivitas Penghimpunan Dana Zakat, Infak, dan Shadaqah Pada Program Ramadhan 1440 H oleh Inisiatif Zakat Indonesia (IZI) Cabang Padang - Revi Hayati; Afra Nadilla; M.S Almuajddedi (ITB AAS INDONESIA Surakarta, 2021)
The purpose of this study was to examine the effectiveness of collecting zakat, infaq and shadaqah funds in the Ramadhan 1440 H program. The Indonesian Zakat Initiative (IZI) Padang Branch is one of the amil zakat institutions in West Sumatra. One of the activities of IZI Padang is to collect zakat funds in the month of Ramadan in 1440 H under the name